A structure-based proposal for a comprehensive myotoxic mechanism of phospholipase A(2)-like proteins from viperid snake venoms - Fernandes, Carlos A. H. [UNESP]; Borges, Rafael J. [UNESP]; Lomonte, Bruno; Fontes, Marcos R. M. [UNESP] (Elsevier B.V., 2014)
Envenomation via snakebites is an important public health problem in many tropical and subtropical countries that, in addition to mortality, can result in permanent sequelae as a consequence of local tissue damage, which represents a major challenge to antivenom therapy. Venom phospholipases A(2) (PLA(2)s) and PLA(2)-like proteins play a leading role in the complex pathogenesis of skeletal muscle necrosis, nevertheless their precise mechanism of action is only partially understood. Recently, detailed structural information has been obtained for more than twenty different members of the PLA(2)-like myotoxin subfamily. In this review, we integrate the available structural, biochemical and functional data on these toxins and present a comprehensive hypothesis for their myotoxic mechanism. This process involves an allosteric transition and the participation of two independent interaction sites for docking and disruption of the target membrane, respectively, leading to a five-step mechanism of action. Furthermore, recent functional and structural studies of these toxins complexed with ligands reveal diverse neutralization mechanisms that can be classified into at least three different groups. Therefore, the data summarized here for the PLA(2)-like myotoxins could provide a useful molecular basis for the search for novel neutralizing strategies to improve the treatment of envenomation by viperid snakes. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Snake venom; Myotoxin; Phospholipase A(2); Lys49; Inhibitor; Myonecrosis